2013
DOI: 10.1097/icl.0b013e31827a7a07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Uptake and Release of Natamycin From Conventional and Silicone Hydrogel Contact Lens Materials

Abstract: All CLs released clinically relevant concentrations of natamycin within 30 minutes, but this release reached a plateau after approximately 1 hour. Further CL material development will be necessary to produce a slow and sustained drug releasing device for the delivery of natamycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 49 publications
4
46
0
Order By: Relevance
“…The drug uptake into all CL materials in this condition ranged between 6.3 and 29.5%, which are comparable to that of a previous study investigating the uptake and release of natamycin from commercial CL materials. [27] The percentage of natamycin released from these materials after 24 h for SH (2.7-13.8%) and conventional hydrogel (CH) (11.0-32.3%) materials are also comparable to results previously reported. [27] The partial release of the drug from the CL material can be attributed to the stronger interaction between the drug and the CL material, in which the equilibrium in an aqueous media highly favors the drug bound to the polymer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The drug uptake into all CL materials in this condition ranged between 6.3 and 29.5%, which are comparable to that of a previous study investigating the uptake and release of natamycin from commercial CL materials. [27] The percentage of natamycin released from these materials after 24 h for SH (2.7-13.8%) and conventional hydrogel (CH) (11.0-32.3%) materials are also comparable to results previously reported. [27] The partial release of the drug from the CL material can be attributed to the stronger interaction between the drug and the CL material, in which the equilibrium in an aqueous media highly favors the drug bound to the polymer.…”
Section: Discussionsupporting
confidence: 88%
“…[26] A previous study examining the uptake of natamycin in dimethylsulfoxide (DMSO), and its release from commercial CLs indicated that this method resulted in a burst release of the drug from the lens materials within the first hour, followed by a plateau phase. [27] To overcome this problem, a second drug delivery platform using colloidal carriers can be incorporated. [28] Colloidal systems, such as liposomes, [29] microemulsions, [30] nanosuspension, [31] and nanoparticles (NPs) [32] are known to provide selective targeting and sustained drug release.…”
mentioning
confidence: 99%
“…On the other hand, no such hydrophobic silicone segments are present in conventional poly-HEMA based hydrogels used in this and other studies [30]. In experiments with polymacon, the lipid deposits were small and were more readily removed by the surfactants in the MPSs.…”
Section: Removal Of Sorbed Lipids By Mpsmentioning
confidence: 83%
“…-(trimethylsilyl)oxy)disiloxanyl)propoxypropyl ester. a Composition components are from Refs [30,36]…”
mentioning
confidence: 99%
“…Simple drug loading methods, such as soaking a commercial CL in pharmaceutical preparations inevitably leads to rapid release kinetics [32]. While different CL material and drug combinations provide different release durations, the overall time frame for drug release is in the order of minutes and is thus not clinically useful [20,33,34]. This is not surprising as commercial CLs are intended solely for refractive error correction, but they are not designed for release of pharmaceuticals.…”
Section: Past Barriers -Contact Lenses Coming Of Agementioning
confidence: 98%